Characteristics of people who rapidly and frequently reattend the emergency department for mental health needs. (October 2016) - Beck, Alison; Sanchez-Walker, Emma; Evans, Lauren J.; Harris, Victoria; Pegler, Ruth; Cross, Sean
Abstract : Objective: This paper identifies the characteristics of emergency department (ED) attendees with a referral to their Mental Health Liaison Service (MHLS) who are at increased risk for rapidly reattending, attending frequently, or attending intensely at this service (which is defined here as rapid and frequent reattendance). Methods: A retrospective 5-year longitudinal study was conducted of all visitors ( n =24 010) attending four busy EDs with a referral to their MHLS from the beginning of 2009 until the end of 2013. A Cox proportional hazards regression was used to identify factors associated with intense use, and a negative binomial regression was used to identify factors associated with frequent attendance. Results: People with certain characteristics were more likely to make 'intense' use of mental health emergency services, which we define as shorter time to reattendance and a higher number of visits over 5 years. The people more likely to make intense use are more likely to have certain clinical diagnoses such as substance misuse, stress disorder, personality disorder and learning disability, to have certain social characteristics such as not being in a relationship, or living alone, and to have healthcare issues such as having been detained under the Mental Health Act and having a greater number of care coordinators over 5 years. Conclusion: Individuals with certain clinical and social characteristics were significantly more likely to reattend EDs and have referral to MHLS rapidly and frequently (i.e. intensely).